May 2015 – A Climate Change in UK Politics. (September 2015) - Hennig, Benjamin; Dorling, Danny
<x xml:space="preserve">Abstract</x> Benjamin Hennig and Danny Dorling plot the geography of an unexpected Conservative General Election victory.